Skill Remoteness and Post-Layoff Labor Market Outcomes - Claudia Macaluso (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper quantifies how the local skill remoteness of a laid-off worker's last job affects subsequent wages, employment, and mobility rates. Local skill remoteness captures the degree of dissimilarity between the skill profiles of the worker's last job and all other jobs in a local labor market. I implement a measure of local skill remoteness at the occupation-city level and find that higher skill remoteness at layoff is associated with persistently lower earnings after layoff. Earnings differences between workers whose last job was above or below median skill remoteness amount to a loss of more than 10,000 over 4 years, and are mainly accounted for by lower wages upon re-employment (not lower hours worked). Workers who lost a skill-remote job also have a higher probability of changing occupation, a lower probability of being re-employed at jobs with similar skill profiles, and a higher propensity to migrate to another city after layoff. Finally, I show that jobs destroyed in recessions are more skill-remote than those lost in booms. Taking all these facts together, I conclude that the local skill remoteness of jobs is an empirically relevant factor to understand the severity and cyclicality of displaced workers' earnings losses and reallocation patterns.
Keywords: E24; J24; J63; 330; mismatch; job loss; worker reallocation; occupational change; migration